2015 Fourth International Conference on Cyber Security, Cyber Warfare, and Digital Forensic (CyberSec) 2015
DOI: 10.1109/cybersec.2015.23
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of SQL Injection Vulnerabilities Assessment of .bd Domain Web Applications

Abstract: Web applications or services play an important role in present day to day life. They have impact on the development of both individual and a country. Easy access to services such as online education, banking, reservation, shopping, resources, and information sharing have been proven most efficient for every day life. Various government and private organizations of Bangladesh have started to use web services to support clients. Most of the web applications of Bangladesh is registered with .bd domain and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Once the database is identified it further the attacks to exploit the system information of the database and the OS or webserver platform as shown in Table 1. As discussed in [13], the SQL was exploitable by syntax of one single quote as what we did in this research project. The number 10 did not exist in the SQL database we injected.…”
Section: Sql Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the database is identified it further the attacks to exploit the system information of the database and the OS or webserver platform as shown in Table 1. As discussed in [13], the SQL was exploitable by syntax of one single quote as what we did in this research project. The number 10 did not exist in the SQL database we injected.…”
Section: Sql Injectionmentioning
confidence: 99%
“…With the syntax of one single quote inserted along the input 10, it makes the database exploitable. Order by query is used to treasure the number of column that exists in the database table and union select or union all select query is used to explore the vulnerable columns in the database table [13]. The usage of these queries can be observed in the sqlmap log file as displayed in Figure 5.…”
Section: Sql Injectionmentioning
confidence: 99%
“…Others conducted case study on different web application vulnerability exploitations in various domains of Bangladesh. A study on three major SQLi techniques implemented on the educational and financial websites of Bangladesh and executes analysis web applications for figuring out the security condition [3], [4]. Another study found on LFI vulnerability and its exploitation techniques based on SQLi and RFI vulnerability in which they examined 153 LFI vulnerable web applications and shown its impact in Bangladesh [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…About 65% of the web applications were vulnerable to single quote (') attack. Another reason of this vulnerability is the development language used to build the web applications [8]. In the dataset 33% of the vulnerable web applications were built using php version 4.9 and older then this as shown in Figure 19.…”
Section: A Dataset 1: Basic Sqlimentioning
confidence: 99%
“…From the rest od the dataset, 4% were built using joomla and 9% were built using Microsoft asp.net. The vulnerability level is identified by the type and amount of data that could be retrieved from attacking the web applications [8]. The statistics of vulnerability level of educational websites of Bangladesh in shown in Figure 21.…”
Section: A Dataset 1: Basic Sqlimentioning
confidence: 99%